Perilaku Dan Status Kebersihan Gigi Dan Mulut Pasca Ceramah Pendidikan Kesehatan Gigi Disertai Diskusi Kelompok Dan Disertai Hands-On - Agustinus Wali (JURNAL INFO KESEHATAN, 2018)
This study aims to determine the differences in the improvement of maternal behavior regarding dental and oral hygiene status and the status of maternal dental and oral hygiene through dental health education lecture methods accompanied by group discussions and lectures with hands-on. The study was conducted on research subjects as many as 95 mothers of children aged 6-8 years who met the inclusion criteria and were divided into two groups. Treatment group I in Benyamin Oebufu PPA IO-497, Kupang City were 53 subjects were given a lecture accompanied by group discussion and group II in Alfa Omega Bakunase 2 PPA IO-495, Kupang City as many as 42 subjects were given lectures with hands-on. The measuring instrument in the study was the questionnaire and the Plaque Index (PI) method. Data analysis using Statistics Program for Social Scince (SPSS) for different tests namely Mann-Whitney test and Wilcoxon Signed Ranks test for abnormal distribution data. The results of the analysis of mean differences between groups in post-test 1 and 2 there were significant behavioral differences in treatment group II higher than in treatment group I (p <0.05), while for dental and oral hygiene status there were no differences in dental hygiene status and mouth between treatment groups I and II. The results of the average analysis of the increase were significant improvements in behavior and dental and oral hygiene status in both treatment groups. The results of delta analysis from pre-test to post-test 1 and pre-test to post-test 2 showed that in the treatment group II the increase in behavior was higher than in the treatment group I (p <0.05), while for dental and oral hygiene status there were no significant differences in dental and oral hygiene status between the two treatment groups (p> 0.05). Dental health education with a lecture method with hands-on further improves the subject's behavior about dental and oral hygiene than the lecture method accompanied by group discussion. Dental health education with lecture methods accompanied by group discussions and lectures accompanied by hands-on both improve dental and oral hygiene status.